2021
DOI: 10.1007/s11606-021-07006-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Prioritizing Workplace Climate Predictors of Burnout Among VHA Primary Care Physicians

Abstract: The views expressed here are solely those of the authors and do not necessarily represent the position of the Veterans Health Administration, United States government, or authors' respective academic institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
(75 reference statements)
1
10
0
1
Order By: Relevance
“…4), both by decreasing the volume of COVID-19 impacted care individuals are providing and the associated personal risk they experience while doing so (direct factors) and by changing the context in which this care is being provided (contextual factors). Although it is important to prospectively test the impact of such interventions, existing evidence supports the efficacy of systematic approaches to identifying and addressing factors that unnecessarily increase workload, while supporting health care workers' control and flexibility, meaning in work, and workplace community 5,[44][45][46] . Identifying and rectifying barriers to communication and transparency within a workplace, providing regular and effective feedback to leadership, and increasing the frontline worker input are often critical intervention components 5,[47][48][49] .…”
Section: Discussionmentioning
confidence: 99%
“…4), both by decreasing the volume of COVID-19 impacted care individuals are providing and the associated personal risk they experience while doing so (direct factors) and by changing the context in which this care is being provided (contextual factors). Although it is important to prospectively test the impact of such interventions, existing evidence supports the efficacy of systematic approaches to identifying and addressing factors that unnecessarily increase workload, while supporting health care workers' control and flexibility, meaning in work, and workplace community 5,[44][45][46] . Identifying and rectifying barriers to communication and transparency within a workplace, providing regular and effective feedback to leadership, and increasing the frontline worker input are often critical intervention components 5,[47][48][49] .…”
Section: Discussionmentioning
confidence: 99%
“…Organizational satisfaction and psychological safety have been previously linked to lower burnout in VA- 5 and non-VA 56 primary care. A small early pandemic study of two VA primary care clinics also showed the association between positive perceptions of the working environment across multiple dimensions (eg, community and fairness) and lower burnout.…”
Section: Discussionmentioning
confidence: 99%
“…30 These demands and resources include literal job demands and resources, like workload or staffing, as well as psychological or environmental demands and resources, like interpersonal conflict or a positive organizational culture. 31 Previous work in VA among behavioral healthcare providers and primary care physicians has shown that reasonable workload, 3,5 adequate resources, 3 and organizational satisfaction 5 are all linked to lower burnout. During the COVID-19 pandemic, healthcare staff were challenged with limited resources, such as a lack of personal protective equipment, shifting workloads, and concern for personal and loved one's safety.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Signs of burnout are reported among more than half of physicians, one third of nursing staff (Reith, 2018), and up to two thirds of mental health workers (Morse et al, 2012). Burnout is also found among VHA providers; one study that examined burnout across all VHA regions (i.e., Veterans Integrated Service Networks) reported that nearly two thirds of primary care providers report some level of emotional exhaustion each week (Sterling et al, 2022). Therefore, there may be an opportunity in the future to consider reshaping existing VA Caring Contact programs (Landes et al, 2021; Reger, Jegley, et al, 2022) to harnesses the passion of veteran advocacy groups (e.g., VSOs), increase suicide prevention, tailor Caring Letters to unique aspects of veteran culture (e.g., peer support), and provide benefits to volunteer letter writers, all without increasing health care professional workload.…”
Section: Discussionmentioning
confidence: 99%